Pengaruh Penerapan Model Pembelajaran Thinking Aloud Pair Problem Solving (TAPPS) terhadap Kemampuan Pemecahan Masalah Matematika - Widya Nusywari; Sudi Prayitno; Junaidi Junaidi; Nurul Hikmah (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2022)
This study aims to determine the effect of the Thinking Aloud Pair Problem Solving (TAPPS) learning model on the mathematical problem solving abilities of eighth grade students of SMP. This research is a quasi-experimental research with Non-Equivalent Control Group Design. The population in this study were all eighth grade students of SMP. In determining the sample, the saturated sample technique was used, where the samples in this study were class VIII-A as the control class and class VIII-B as the experimental class. The instrument used in this research is a test of mathematical problem solving ability on number pattern material. Quantitative data analysis was performed using a gain t-test. The results of data analysis obtained thitung = 2.14 and ttable = 2.064 so that thitung > ttable then H0 is rejected which indicates that there are differences in students' mathematical problem solving abilities between classes that receive TAPPS learning and direct learning. This shows that learning with the TAPPS model has an effect on the mathematical problem solving abilities of eighth grade students of SMP. The influence of the application of the Thinking Aloud Pair Problem Solving (TAPPS) learning model on the mathematical problem solving ability of class VIII students at SMP on the number pattern material using the effect size formula (d) is 1.907, which means that the effect given has a high category.